Asian Indians, coronary artery disease, and physical exercise - Dhawan, J (1997)
Objective—To evaluate the relation of physical activity to different clinical and biochemical risk factors for coronary artery disease among people from different ethnic groups with angiographically proven coronary artery disease. Subjects—British Asians, Indian Asians, and white people suffering from coronary artery disease, and their respective controls. Interventions—History, physical examination, coronary angiography (at baseline), laboratory investigations. Main outcome measures—Relation of physical activity level to serum insulin, glucose, cholesterol, triglycerides, and high density lipoproteins, systolic and diastolic blood pressures, and body mass index in patients and controls. Results—391 male patients were studied, of whom 260 (66.5%) were classified as sedentary. Mean serum insulin at 0, 1, and 2 hours after 75 g oral glucose was higher among the sedentary population (17.1 v 11.6, 88.2 v 62.1, and 57.9 v 36.2 µU/ml, respectively (all p < 0.0001). Mean body mass index was also higher among the sedentary population (25.53 v 23.95, p < 0.0001), as were mean serum triglycerides (1.85 v 1.60 mmol/l, p < 0.01) and systolic and diastolic blood pressures (133.9 v 129.4, p < 0.05, and 81.1( )v 79.0, p < 0.01). There was no difference in the mean serum cholesterol and high density lipoprotein between the two groups. British Asians were the most sedentary and Indian Asians the most physically active. Conclusions—There are marked differences in the level of physical activity among the various ethnic groups in the United Kingdom. In each ethnic group, physical activity reduced mean serum insulin, body mass index, and serum triglycerides and had a favourable effect on systolic and diastolic blood pressures. Promotion of physical activity could be of value for the Asian community in the United Kingdom.   Keywords: coronary artery disease;  physical activity;  British Asians;  Indian Asians